Discussion of Handling Delays in Malaysian Government Projects via PMBOK Knowledge Areas : Learning from Project Management Failure - Ng Wai Kit; Luu Wei Chek; Lim Kar Nee; Kor Wei Yan; Yau Jia Yin; Khoo Jia Hen; Chong Wen Zhe; Lui Yi Wen; Mazidah Mat Rejab (Applied Information Technology And Computer Science, 2023)
With an emphasis on developing public infrastructure, the Malaysian government played a vital role in the regional construction market. On the other hand, prolonged project timeframes and cost overruns have resulted from delays in government projects, which are ascribed to poor project management. With an emphasis on comprehending the roles played by customers, contractors, and consultants in project delays, this study attempts to look into the underlying causes of these delays. This study uses questionnaire surveys as its primary research approach in an effort to gain important insights into the variables causing these delays. The results will highlight important patterns and trends in ineffective project management. The findings of this study will provide the groundwork for further initiatives aimed at improving project management in Malaysia’s construction industry.